Edukasi Gaya Hidup Sehat Untuk Meningkatkan Literasi Kesehatan Siswa SMK - Devi Andreawati; Agustiyani Wijayanti; Nak Mas Ashim Hanif; Atikawati Fadhillah; Muhammad Rio Satriananta; Nur Aminullah; Yeni Rahmawati; Januar Abdillah Santoso (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2026)
This study aims to describe the level of healthy lifestyle practices and health literacy among students at SMK Negeri 2 Tenggarong as a basis for strengthening adolescent health promotion programs. A descriptive quantitative design was employed using a questionnaire consisting of four key indicators: healthy eating habits, physical activity, rest and mental health, as well as hygiene and healthy behavior. A total of 192 students participated as respondents and completed a four-point Likert scale questionnaire. The results indicate that most students demonstrated moderate to high levels of healthy lifestyle practices. In terms of eating habits, the majority reported regular breakfast consumption, adequate intake of fruits and vegetables, and limited consumption of sugary drinks. Students also showed good physical activity levels, with many actively engaging in sports and daily movement. The rest and mental health indicator revealed that most students had sufficient sleep duration and stable emotional conditions, although late-night gadget use remained an issue for some. Hygiene practices were generally high, reflecting strong awareness of personal and environmental cleanliness. Overall, the findings suggest that students' health literacy is relatively good, yet continuous reinforcement through school-based socialization and educational interventions is needed to ensure consistent and sustainable healthy behaviors.